The Intersection of Organizational Identity, Knowledge, and Practice: Attempting Strategic Change Via Knowledge Grafting - Nag, Rajiv; Corley, Kevin G.; Gioia, Dennis A. (Academy of Management Journal, 2007)
We investigated the attempt of a high-technology R&D organization to transform into a market-oriented organization by “grafting” new, nontechnological knowledge. The intended strategic transformation did not succeed for reasons with wide implications for theory and research. Our findings suggest that the intersection of organizational identity, knowledge, and practice hindered the development of the new knowledge and undermined the broader strategic transformation effort itself. The failure of the graft revealed a previously underrecognized relationship between identity and knowledge that manifested itself in organization members' efforts to preserve the collective practices that characterized how they used knowledge in accomplishing their work.